Efektivitas Media Visual dalm Meningkatkan Pengetahuan tentang Seribu Hari Pertama Kehidupan Remaja Putri: The Effectiveness of Audio Visual Media in Increasing Knowledge About the First Thousand Days of Life Young Women - Sunaeni Sunaeni; Inayah M Abduh; Mariana Isir (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
Background: Understanding nutrition in the first thousand days of human life needs to be promoted in preventing stunting. Adolescent girls have a key role in maintaining health during pregnancy, of which 28.72% of women in West Papua aged 15-19 years (SMP-SMA) are pregnant for the first time. Audio-visual media can be used as an alternative in disseminating information on stunting prevention during the